“Early Rupture of Membranes” during Induced Labor as a Risk Factor for Cesarean Delivery in Term Nulliparas - Lee, Seung Mi; Park, Jeong Woo; Park, Chan-Wook; Yoon, Bo Hyun (PLOS ONE, 2012)
Objective To determine if “early rupture of membranes” (early ROM) during induction of labor is associated with an increased risk of cesarean section in term nulliparas. Study Design The rate of cesarean section and the timing of ROM during the course of labor were examined in term singleton nulliparas whose labor was induced. Cases were divided into 2 groups according the timing of ROM: 1)“early ROM”, defined as ROM at a cervical dilatation<4 cm during labor; and 2) “late ROM”, ROM at a cervical dilatation≥4 cm during labor. Nonparametric techniques were used for statistical analysis. Results 1) In a total of 500 cases of study population, “early ROM” occurred in 43% and the overall cesarean section rate was 15.8%; 2) patients with “early ROM” had a higher rate of cesarean section and cesarean section due to failure to progress than did those with “late ROM” (overall cesarean section rate: 24%[51/215] vs. 10%[28/285], p<0.01; cesarean section rate due to failure to progress: 18%[38/215] vs. 8%[22/285], p<0.01 for each) and this difference remained significant after adjusting for confounding variables. Conclusion “Early ROM” during the course of induced labor is a risk factor for cesarean section in term singleton nulliparas.